(untitled) (Bangladesh Journal of Infectious Diseases, 2025)
Background: Antimicrobial resistance (AMR) presents a significant global health threat, driven by the misuse and overuse of antibiotics. Objective: The purpose of the present study was to assess the knowledge, attitudes, and practices (KAP) regarding antimicrobial stewardship among healthcare professionals working in public hospitals in Bangladesh. Methodology: This cross-sectional survey was conducted at Communicable Disease Control (CDC) unit of the Directorate General of Health Services (DGHS) of Ministry of Health and Family Welfare, Dhaka, Bangladesh from September 2022 to October 2022 during a national orientation program for physicians from government healthcare facilities across Bangladesh. Physicians from facilities with indoor patient services were invited, excluding tertiary medical hospitals. The participants who agreed to take part in the survey through written consent were included in the study. A pre-tested, semi-structured questionnaire was designed to assess their knowledge, attitudes, and practices (KAP) regarding antimicrobial stewardship and AMR. Results: The survey involved 292 physicians, primarily male and aged between 25 and 35 years. The results revealed a high level of general awareness about AMR, with 95.2% acknowledging the role of antimicrobial stewardship programs (ASP) in reducing resistance. The participants uniformly agreed with the importance of infection prevention and control (IPC). However, there were significant gaps in understanding specific ASP-related concepts, such as Defined Daily Dose (DDD) and antibiograms, with 41.0% to 75.0% of respondents either unfamiliar with or unsure about these terms. Attitude related responses indicate strong support for educational programs and the integration of ASPs into hospital settings, with 99.0% advocating for training on rational antibiotic use. In practice, most respondents reported rational antibiotic prescribing, yet inconsistencies remain in areas like the choice of antimicrobials and adherence to stewardship principles. Conclusion: The findings have revealed a gap between knowledge and practice concerning AMR, emphasizing the need for targeted educational interventions, structured policies, enhanced training, and robust Antimicrobial Stewardship Programs implementation to mitigate AMR and improve patient outcomes in Bangladesh. Bangladesh Journal of Infectious Diseases, June 2025;12(1):18-26